A Taxonomic study of the Eulophid parasitoids (Hymenoptera: Chalcidoidea) of leafminers in Latakia province - مــهنـا رزق; نبيل أبو كف (Latakia University Journal -Biological Sciences Series, 2022)
In this study, 219 Eulophidae specimens were collected from 12 locations in Latakia province during 2020. Morphological and taxonomical aspects of the collected specimens have been studied. Identification key of recorded species is given according to the most important taxonomic features. A total of five species are recorded and classified, and these are: Neochrysocharis formosa, Chrysocharis polyzo, Semielacher petiolatus, Diglyphus crassinervis, Diglyphus isaea. The following species Chrysocharis polyzo and Diglyphus crassinervis are considered the first ever recorded in syria.